Convencionalismo e naturalismo em Rousseau - Pagliaro, Heitor de Carvalho (2013)
This dissertation investigates the concept of law in Rousseau, analyzing if he defends the idea of natural law or if he is a conventionalist. Some commentators, like Robert Derathé, conceive Rousseau as a naturalist, as opposed to others, like Charles Vaughan, who think that he is a conventionalist. Here we will critically assess those positions and will try to se if they exclude each other or if Rousseau can be read, somehow, as defending fundamental aspects of those two positions.